Properties of Aluminosilicate Refractories with Synthesized Boron-Modified TiO2 Nanocrystals - Claudia Carlucci; Francesca Conciauro; Barbara Federica Scremin; Antonio Graziano Antico; Marco Muscogiuri; Teresa Sibillano; Cinzia Giannini; Emanuela Filippo; Caterina Lorusso; Paolo Maria Congedo; Giuseppe Ciccarella (Nanomaterials and Nanotechnology)
An efficient microwave supported synthesis, with a reaction time of only one and a half minute, to prepare boron-modified titania nanocrystals TiO2:(B), was developed. The nanocrystals were obtained by hydroly‐ sis of titanium tetraisopropoxide (TTIP) together with benzyl alcohol and boric acid, and the approach did not need surfactants use and a final calcination step. The produced TiO2:(B) nanocrystals were characterized in detail by low magnification Transmission Electron Microscopy (TEM), Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES), X-Ray Diffractometry (XRD), and a Micro Raman Spectroscopy. One of the obtained samples was then tested as an additive in various amounts in a typical aluminosilicate refractory composition. The effects of these additions in bricks were evaluated, according to UNI EN 196/2005, in terms of thermo-physical and mechanical properties: diffusivity, bulk density, apparent density, open and apparent porosity and cold crushing strength. Bricks’ microstruc‐ ture was analysed by Scanning Electron Microscopy (SEM) and energy dispersion spectroscopy (EDS). The bricks obtained with nanoadditives presented improved mechanical characteristics with respect to the typical aluminosilicates, presumably because of a better compac‐ tion during the raw materials’ mixing stage.